THE PHENOMENON OF DIMLY LIT STALLS ALONG THE NORTH COAST ROAD (CASE STUDY OF INDIRECT FEMALE SEX WORKERS) AGAINST THE SPREAD OF SEXUALLY TRANSMITTED DISEASES IN JENU SUBDISTRICT TUBAN - Utami, Aris Puji; Faizah, Hanim Nur; Mubarok, Moh. Wafi (Journal of Vocational Nursing, 2021)
Introduction: Cases of STIs continue to soar, one of which is due to the practice of prostitution because women sex workers (WPS) are one of the high risk groups of contracting and transmitting STIs. The purpose of this study was to explore knowledge and explore the behaviour of women sex workers indirectly. Methods: The design of this research uses descriptive qualitative research method with phenomonology. The subject of this study was women indirect sex workers who sold sexual services in exchange for money located in the village stalls of Sugiwaras District Jenu Tuban District a number of five women sex workers. Data collection techniques used in this research are observation and structured interview techniques. Result: The results of this study showed that participants' knowledge of reproductive health was not good, as evidenced by the women sex workers were not immediately able to explain the definition, signs and symptoms and how to prevent the spread of sexually transmitted infections (STIs). In terms of applying behaviour, participants were classified as negative because all participants revealed to have had unless condomless sexual intercourse and economic difficulties. Conclution: The sexual behaviour of female sex workers indirectly in the stalls along the pantura was classified as negative because all participants revealed to have had sexual intercourse without condoms and economic difficulties. Female sex workers also have low knowledge of STI.